CEFR-Based Beginner Arabic Reading And Writing Curriculum Design In Indonesia/ Desain Kurikulum Membaca dan Menulis Bahasa Arab Pemula Berbasis CEFR di Indonesia - Talqis Nur Dianto; Nanang Joko P; Ahmad Fatoni; Salsabila Kalita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to provide a reference for developing a curriculum for learning to read and write Arabic for beginners based on CEFR at levels A1 and A2. The design of the reading and writing learning curriculum used in Indonesia refers to the level of formal education that is not by the level of student ability, making it difficult to understand and boring for novice students. Learning foreign language skills is carried out in stages according to the power of students, not based on their level of formal education. Learning Arabic in Indonesia gives the impression that it is not yet effective from the objectives, materials, methods, media, and teaching evaluations that appear to repeat the next level of learning from the goals, topics, and study materials. Arabic learning based on CEFR is an alternative to learning Arabic in Indonesia in stages in six levels A1, A2, B1, B2, C1, and C2. This research uses the descriptive analysis method to design the early reading and writing curriculum based on CEFR theory. Curriculum validation is carried out by experts in Arabic language learning so that it becomes a better learning curriculum than before. Curriculum design for reading and writing Arabic for beginners at levels A1 and A2 covers essential elements, including objectives, materials, methods, media, and evaluation. The results showed that learning to read and write Arabic can be developed with the CEFR theoretical approach and used in learning Arabic for beginners.